2008
DOI: 10.1016/s1808-8694(15)31097-1
|View full text |Cite
|
Sign up to set email alerts
|

Deep neck infection - analysis of 80 cases

Abstract: Airway control should be priority in managing deep neck infections and if the patient has to be submitted to surgery special care should be taken at the moment of intubation - when curare must never be used. CT scan is the gold-standard imaging evaluation for the diagnosis of deep neck infection. Morbi-mortality is high when associated with septic shock and mediastinitis. Our mortality rate was 11.2% and only one, in five patients with mediastinitis, survived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
2
19

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 24 publications
9
49
2
19
Order By: Relevance
“…It is widely known that delayed diagnosis and inadequate mediastinum drainage are important factors associated with an increased incidence in mortality. 14,[16][17][18][19] In our study, the mortality rate was 0.44 per cent, and the only case of death was not related to delayed diagnosis but to the co-existence of severe co-morbidities known to worsen the prognosis of deep neck infections. 16 Multivariate analysis showed that patients with diabetes mellitus and a laterocervical abscess had a higher risk of developing complications.…”
Section: Discussionmentioning
confidence: 80%
“…It is widely known that delayed diagnosis and inadequate mediastinum drainage are important factors associated with an increased incidence in mortality. 14,[16][17][18][19] In our study, the mortality rate was 0.44 per cent, and the only case of death was not related to delayed diagnosis but to the co-existence of severe co-morbidities known to worsen the prognosis of deep neck infections. 16 Multivariate analysis showed that patients with diabetes mellitus and a laterocervical abscess had a higher risk of developing complications.…”
Section: Discussionmentioning
confidence: 80%
“…10-12. Contrast enhanced CT scan is investigation of choice with sensitivity of 100% in evaluation of deep neck space infections. 13 CT scan is also very sensitive in detection of known complications like mediastinitis, jugular vein thrombosis. CT or USG guided aspirations of abscess are successful in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Etiyolojide yetişkinlerde ilk sırayı odontojenik nedenler alırken, çocuklarda tonsillitler almaktadır (Parhiscar ve Har-El, 2001;Agarwal et al, 2007;Marioni et al, 2008). Tanıda, tercih edilen radyolojik yöntemler; direkt grafiler (lateral servikal grafi , PA akciğer grafisi , panoramik mandibula grafisi), bilgisayarlı tomografi, manyetik rezonans görüntüleme ve ultrasonografidir (Parhiscar ve Har-El, 2001;Marioni et al, 2008;Suehara et al,2008). Kliniğimizde sıklıkla anatomik ilişkilerin, kemik yapının ve hava pasajının değerlendirilmesinde etkinliği nedeniyle BT'yi tercih etmekteyiz.…”
Section: Discussionunclassified